(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
India has a rich and hoary tradition of story – telling,a brilliant galaxy of story – tellers who illumine the pages of her history andliterature. Bankim Chandra Chatterjee’s Rajmohan’s wife (1864), which istypical of a transitional period in the history of Indian literature was thefirst attempt made by an Indian to produce a novel in English. Later thenovelists like Mulk Raj Anand, R.K.Narayan, Raja Rao, Bhabani Bhattacharya,Manohar Malgonkar, Ruth Prawar Jhabvala, Anita Desai, Chaman Nahal, Arun Joshi,Salman Rushdie, Amitav Ghosh, Kamala Markendeya, Nayanatara Sahgal, ArundhatiRoy, and several others have made their contribution for the flourishment of IndianEnglish fiction.